Can someone please explain to me how to solve this?

For x≥0, [tex]\sqrt{x^5}[/tex] + [tex]\sqrt{9x}[/tex] =

(A) (x²+ 3)√x

(B) 10[tex]\sqrt{x^6}[/tex]

(C) [tex]\sqrt{x^5+9x}[/tex]

(D) x²+ 3

(E) 3x²

Respuesta :

Answer:

A

Step-by-step explanation:

√(x^5) = x^(5/2) = (x^2)√x

√9x = (√9)(√x) = (3)√x

which means: ((x^2)√x) + ((3)√x)

since both have a √x, you can factor it out. for example...if you look at A, if you apply the distributive property you can see it expands back out. hmu if you need a different. explanation